Total and differential white blood cell counts and hemodynamic parameters in first-episode psychosis - Moody, Grant; Miller, Brian J. (Psychiatry research, 2018)
There is evidence for blood inflammatory abnormalities in patients with first-episode psychosis (FEP). The monocyte- and neutrophil-to-lymphocyte ratios (MLR; NLR) are markers of inflammation and endothelial dysfunction, and predictors of cardiovascular disease, the leading cause of death in schizophrenia. We investigated relationships between white blood cell (WBC) counts and hemodynamic parameters associated with cardiovascular disease risk in 25 subjects age 18–50 hospitalized for FEP and 44 controls. Subjects had a blood draw, vital signs, and medical history. Patients with FEP had significantly higher NLR, MLR, pulse pressure, and rate pressure product (RPP) than controls (p < 0.05 for each), after controlling for potential confounders. In linear regression analyses, higher monocytes were a significant predictor of higher pulse pressure (p = 0.033) and higher MLR predicted RPP at the trend level (p = 0.051) in FEP, after controlling for potential confounders. To our knowledge, ours is the first report of increased RPP, a measure of myocardial workload, in FEP. We also replicated findings of increased NLR, MLR and pulse pressure in FEP. Our findings underscore that measurement of routine vital signs and blood total and differential WBC counts are germane to the clinical care of patients with psychosis as markers of cardiovascular disease risk. •Patients with first-episode psychosis (FEP) had increased inflammation.•Patients with FEP also had increased hemodynamic parameters.•White blood cell counts (WBC) were predictors of hemodynamic parameters.•Routine vital signs and WBC counts are germane to the clinical care of patients with psychosis as markers of cardiovascular disease risk.